MORPHOMETRIC OF THE REPRODUCTIVE ORGAN OF FEMALE BANDICOOT-THE COMMON ECHYMIPERA (Echymipera calubu) - Angel N Tethool; Fahry Rafli; Freddy Pattiselanno (Scripta Biologica, 2022)
A study was conducted at the Laboratory Animal Physiology and Reproduction Laboratory, Faculty of Animal Science Universitas Papua between 15 June and 15 September 2017. Three female reproductive organs of bandicoot (Echymipera kalubu) were used, and the morphology of the reproductive organ was examined. This paper presents relevant data for further marsupial reproduction studies.